When life is an itch: What harms, helps, and heals from the patients' perspective? Differences and similarities among skin diseases. Issue 4 (9th June 2020) - Chee, Alvyn; Branca, Lorenzo; Jeker, Florence; Vogt, Deborah R.; Schwegler, Simon; Navarini, Alexander; Itin, Peter; Mueller, Simon M.
Abstract: Itch is the commonest skin‐related symptom, associated with a high psychosocial and economic burden. While the main focus of itch research lies on a few chronic skin diseases, only little is known about the perception of itch, itch‐aggravating/‐relieving factors and treatment preferences in patients with acute and chronic itch of various etiology. In this cross‐sectional study, we assessed these aspects in 126 patients (mean age 61.7 ± 18.4 years, 67 females, median itch duration 3.9 years) using a 78‐item questionnaire. The diseases were categorized into 11 diagnostic groups for descriptive analysis; the three most frequent groups ("atopic dermatitis, " "nonatopic eczema, " "inflammatory dermatoses") were statistically compared. Itch was most often perceived as localized 42.9%, burning (40.5%), and worrying (39.7%) with worsening in the evening (49.2%), due to warmth (42.1%) and sweating (26.2%). While itch perception, itch‐aggravating factors and treatment preferences differed broadly among patients, the itch‐relieving personal strategies were more uniform ("scratching by hand 70.6%, applying topicals 57.9%). Also, 69.8% of patients suffered from itch‐related sleep disturbance, consequently affecting their relatives in 30.0%. Subgroup comparisons revealed significant differences regarding itch‐aggravating factors ( P = .0012) and itch duration ( P = .0082). Patients rated the antipruritic effectiveness of phototherapy, "complementary and alternative medicine" and "other tablets" as high, but oral antihistamines, "cortisone tablets" and any topical as only moderately efficacious. The preferred administration of an ideal itch treatment was "creams/ointments" (51.6%) or "tablets" (35.7%), only few patients preferred "injections" or "patches." Consideration of such differences and similarities in itch characteristics and treatment preferences could help to better tailor treatment in itch patients.